CONCEPT DESIGNING OF VIDEO PROFILE FASHION PROGRAM UNIVERSITAS NEGERI MALANG - Aini, Nurul (EARR (Educational Administration Research and Review), 2020)
This study aims to describe the concept of designing a profile video for the Fashion Program through the initial stages of the creation method, namely the pre-production stage or about how it is planned. Video profiles are very effective media that are used to promote a particular area, product, and promote a particular company. In this case the profile video that will be made is the profile video of the Fashion Program at Universitas Negeri Malang. This research was conducted because the Fashion Program did not yet have a profile or company profile video that was indispensable for  Program to promotion and information facilities. Pre-production stages that are often done in pre-production include 3 things, namely synopsis, script and storyboard. Later in this article, we will discuss in detail how the three stages of the process are created.